Molecular Basis of Plant-Symbiotic Fungi Interaction: An Overview - Singh, Anjana (Scientific World, 2010)
The intimate symbiotic relationships developed between mycorrhizal fungi and plants, since land colonization by the latter have led to an interdependence between these organisms for many basic processes. The fungi require plants to accomplish their life cycle. Plants depend heavily on mycorrhizal fungi for many different functions, such as mineral nutrition, and abiotic and biotic stress resistance. Substantial evidence has accumulated in recent years about how rational use of this microsymbiont could significantly contribute to decreasing use of fertilizer and pesticide in agriculture, forestry and flori-horticulture, especially, if combined with other beneficial soil microorganism. Symbiotic fungi act as major link between plants and soil, and should, therefore, be considered a central pivot for new strategies in the development of biologically-oriented agricultural practices. To search for functional genes controlling fungal morphogenesis, infection process, metabolism of mycorrhizal roots, down regulation of defense- related genes in plants, are still in infancy, but with the advent of new molecular biology techniques, it is speculated not to be a far cry. And it is hope that it will cover the experimental and technical gap, still existing between the AM and other symbiotic systems which are experimentally more tractable. Plants with constitutively over-expressed defense related genes provide interesting material of determining how fungi contend with plant defense, although, how modification occurs in the expression of other genes in such plant is unclear. Molecular investigation of isogenic myc- mutants from pea and more recently from M. truncatula should also significantly advance our knowledge of plant and fungal gene expression essential to the symbiosis. Polypeptide analysis has already shown those compatible interactions in mycorrhizal pea and tobacco roots are dominated by de novo gene expression. Incompatible interaction in myc- mutant pea roots are mainly characterized by a down regulation of polypeptide synthesis, suggesting that maintenance of the activity of constitutively expressed plant genes may be important in the establishment of symbiotic fungus. The precise signals and molecular mechanism in establishing cellular and functional compatibility in fungal plant symbiosis are unknown. Rapid evolution in molecular techniques is facilitating the possibility of analyzing temporal and spatial gene expression in the two partners. Furthermore, cloning of genomic DNA has been achieved for uncultivable fungi and hybridization with homologous or heterologous probes is opening a vast new area of research for identifying genes essential to the different life stages of these organisms. Moreover, approaches like differential RNA display offers alternative strategies for studying the expression and regulation of those fungal genes underlying molecular mechanisms involved in the establishment, maintenance and functioning of the symbiosis. Mycorrhizal research presents a challenging and exciting period when molecular and genetical tool can be used synergistically. The development of techniques permitting studies of the mycorrhizal fungi, which are at best difficult to culture, will expand our understanding of the value and functioning of below-ground root-fungal symbiosis. The author has screened a novel symbiotic fungus Piriformospora indica. This is a cultivable root colonizing and plant promoting fungus. Another fungi of relevance are species of Sebacina and Geosiphon. Some information on the interaction of P. indica with conventional non-host Arabidopsis thaliana is indicated. The author believes that there are many tools for the analysis of the genetic component of the specific biological question and further hopes that this article shall open vistas and thoughts for further challenging new research. Key Words: Colonization; Microsymbiont; Gene expression; Piriformospora indica. DOI: 10.3126/sw.v5i5.2668 Scientific World, Vol. 5, No. 5, July 2007 115-131